Upper eyelid reconstruction using an advancement tarso-conjunctival flap. Issue 6 (November 2022) - Awad, Mary; Wilde, Craig; Albanese, Giorgio; Abercrombie, Lorraine
Purpose and context: Upper eyelid reconstruction is particularly complex due to its functional and aesthetic importance. We aim to assess the outcomes/ complications of patients who undergo upper eyelid reconstruction of the posterior lamellae with an advancing tarsonconjunctival flap from the same affected eyelid, following excision of a periocular malignancy by Mohs Micrographic Surgery. Method: A retrospective consecutive case note review of all eight patients who underwent the procedure between May 2016 and Jan 2021 were included. Patient demographics and factors influencing outcomes (smoking status, use of blood thinners, past medical/ drug history, size/location of the defect), follow up duration and complications were recorded. Key results: Minor post-operative complications included an eyelid notch and retraction. There was one patient with lagophthalmos, but no exposure keratopathy. Two patients had misdirected lashes, one requiring electrolysis. Both monocular patients, who required the procedure in their only seeing eye, and were unable to tolerate a compressive dressing, had wound dehiscence. One patient was on steroids and the other on warfarin and a diabetic. No vision loss ensued and no-one underwent surgical revision. Follow up ranged from 4–52 months. Conclusions: An advancing tarso-conjunctival flap is an expedient single-stage reconstructive technique that can be used to reform up to two- thirds of the posterior lamellae in full thickness upper eyelid defects involving the lid margin. Complications are minor. It is of particular benefit in patients where occlusion of the visual axis is unacceptable, although the risk of wound dehiscence is high. This technique forms a valuable part of the systematic reconstructive algorithm.